JUDGE’S DECISION ON WORK TERMINATION DISPUTE IN INDONESIA AFTER CONSTITUTIONAL COURT DECISION NUMBER 37/PUU-IX/2011 - Neni Vesna Madjid; Saldi Isra; Kurnia Warman; Mardenis Mardenis (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Testing the provision of Article 155 section (2) Law Number 13 of 2003 on Manpower has been decided by the Constitutional Court (CC) through decision Number 37/PUU/IX/2011. Prior to the Constitutional Court decision, there are many various interpretations of undetermined clause. The Constitutional Court firmly states that the undetermined clause must be interpreted as “having a permanent legal force